A Review of Lekhana Basti in the Management of Sthoulya (Obesity) - Ramniwas; Gupta, Arvind; Barmola, Roopali (International Research Journal of Ayurveda & Yoga, 2025)
Introduction: Sthoulya, or obesity, is a major metabolic disorder in Ayurveda, primarily resulting from the stagnation of Meda Dhatu (fat tissue) and the impairment of Agni (digestive and metabolic fire), compounded by the vitiation of Kapha and the subsequent obstruction-induced aggravation of Vata Dosha. This condition is categorized under Santarpana-uttha Vyadhi (diseases of over-nourishment), mandating Apatarpana (reduction) therapy. Ayurveda provides a variety of therapeutic techniques, with Panchakarma being a significant treatment modality. Lekhan Basti, a Panchakarma treatment that involves medicated enemas, has shown substantial potential in the management of obesity, dyslipidemia, and metabolic diseases, particularly those caused by excess Kapha and Medodhatu. Materials and Methods: According to Acharya Sushruta and Acharya Sharangdhara, Lekhan Basti has Triphala Kwatha, Gomutra, Madhu, Yavakshara, and Ushakadi Gana. Kapha Shamaka, Deepana, Tiksna, and Agni Deepana are among the components with known medicinal potential. The process involves the use of an alkaline formulation due to components such as Gomutra and Yavakshara, which promote quick absorption and improve gut flora. Results: Lekhan Basti has a wide range of therapeutic effects, including correcting metabolic imbalances and reducing excess Kapha and Medodhatu. It has been believed to include qualities such as Vata-Kapha Shamaka, Deepana, Pachana, Lekhana, Karshana, and Srotoshodhaka, which aid in fat loss, digestive fire, and detoxification. Discussion: Lekhan Basti is an excellent Samshodhana treatment for Sthoulya. It is a potential strategy to enhance general metabolic health since it balances Kapha and reduces excess Medodhatu. Its detoxifying qualities, together with its effect on gut flora, make it an essential treatment for metabolic diseases. Conclusion: Lekhana Basti is effective as a Samshodhana (cleaning) therapy for metabolic illnesses caused by high Kapha and Medodhatu, including Sthoulya (obesity), dyslipidemia, PCOS, and other lifestyle diseases.